Advanced Triage Protocol: The Role of an Automated Lactate Order in Expediting Rapid Identification of Patients at Risk of Sepsis in the Emergency Department. (19th August 2022) - Baum, Andrew; Carr, Brendan G.; Perman, Sarah M.; Barger, Jennifer; Goyal, Munish; Gaieski, David F.
Abstract : OBJECTIVES: We undertook a process improvement initiative to expedite rapid identification of potential sepsis patients based on triage chief complaint, vital signs, and initial lactate level. DESIGN: Prospective cohort study. SETTING: Seven hundred-bed tertiary care hospital with ≅65, 000 patient visits/yr. PATIENTS: Patients presenting to emergency department (ED) triage who met the following criteria: greater than or equal to two of the three systemic inflammatory response syndrome criteria assessable in triage, a chief complaint suggestive of infection, emergency severity index 2 or 3, and ambulatory to ED. INTERVENTIONS: A computer-generated lactate order was created, staff education and resources increased, and point-of-care lactate testing was introduced. MEASUREMENTS AND MAIN RESULTS: Primary endpoints include the following: percent of patients having a lactate level drawn, percent of lactate samples resulting before room placement, and time intervals from triage to lactate blood draw and to lactate result. Secondary endpoints were percentage of patients admitted to the hospital, percentage admitted to the ICU, and in-hospital mortality. Six thousand nine hundred six patients were included: 226 historic controls (HCs) and 6, 680 intervention group patients. The mean serum lactate level was 1.77 ± 1.18 mmol/L. The percentage of patients having a lactate resulted increased from 27.4% in the HC period to 79.6%. The percentage of these lactate results available while the patient was still in the waiting room increased from 0.4% during the HC period to 33.7% during Phase 5 ( p < 0.0001). In the intervention period, time from triage to lactate result decreased (78.1–63.4 min; p < 0.0001) and time to treatment room decreased (59.3–39.6 min; p < 0.0001). CONCLUSIONS: Implementation of a computerized lactate order using readily available data obtained during ED triage, combined with point-of-care lactate testing, improves time to lactate blood draw and lactate result in patients at risk for severe sepsis. Initial lactate levels correlated with admission to the hospital, admission to the ICU, and in-hospital mortality.